MENAKARKEKUATAN SIMBOL AGAMA DALAM KONTESTASI POLITIK LOKAL - Agus Agus (Universitas Islam Negeri (UIN) Mataram, 2017)
The election of governors, regents, mayors directly by the people, then known as direct elections, has been held since 2005. Until now, the phenomenon of elections shows a variety of political uniqueness in the region. Plurality of Indonesia is the nature of election elections. NTB as an area with a Muslim majority became a fertile ground of religious symbol awakening on the political stage. In the 2008 election, the religious symbol user was TGH. M. Zaenul Madjdi, paired with Ir. H. Badrul Munir, MM. They won the election with 38.85% of the valid votes. Similarly, in the 2013 election, two users of religious symbols; TGH. Zaenul Madjdi and Dr. KH. Zulkifli Muhadli became the first and second most votes. TGH. Zaenul Madjdi who is paired with H. Muh. Amin obtained 44.36%. While Dr. KH. Zulkifli Muhadli paired with Prof. Dr. Ir. H. Muhammad Ichsan earned 26.51%. From the perspective of symbolic interactionism, introduced by George H. Mead, found four stages of voter action, namely impulse, perception, manipulation, and consumption. From these three stages, it seems that the use of religious symbols in direct elections is able to accelerate voter choice on candidates, before voters reach the polling stations.